Exploring strengthening mechanism of FeCoNiAl high-entropy alloy by non-metallic silicon addition produced via powder metallurgy - Lee, Hansung; Sharma, Ashutosh; Ahn, Byungmin (Journal of Alloys and Compounds, 2023)
Multi-component high-entropy alloys (HEAs) have recently attracted interest in balancing the bottleneck of high hardness and high fracture toughness. This study demonstrates the influence of Si addition to FeCoNiAl HEA fabricated by advanced powder metallurgy. The FeCoNiAlSix (x = 0, 0.2, 0.4, 0.6, and 0.8 molar ratio) HEA was fabricated by mechanical alloying for 45 h and subsequent powder compact densification by spark plasma sintering (SPS). FeCoNiAlSix HEA morphology and phase evolution were investigated to understand the influence of Si content on the microstructure, compressive strength, and fracture mechanisms of the FeCoNiAl alloy. The results indicate that FeCoNiAlSix powders HEAs have single-phase body-centered cubic (BCC) structures. However, densification of powders HEAs facilitates dual-phase face-centered cubic (FCC) and BCC formation in FeCoNiAl, whereas the FCC phase transforms completely to BCC or BCC/B2 with Si addition. The Vickers microhardness of sintered FeCoNiAlSix HEAs varies from 524 HV (for FeCoNiAl HEA) to 798 HV (for FeCoNiAlSi0.8 HEA). The maximum compressive strength of HEAs varies from 1325 MPa (for FeCoNiAl HEA) to 2031 MPa (for FeCoNiAlSi0.8 HEA), respectively. The absorption energies of FeCoNiAl and FeCoNiAlSi0.2 were 198 and 203 MJ/m3, respectively. In contrast, the absorption energies of FeCoNiAlSi0.6 and FeCoNiAlSi0.8 HEAs reduced drastically (115 and 96 MJ/m3, respectively). The failure mechanism of the FeCoNiAlSix HEAs was a mixed ductile-brittle fracture in FeCoNiAl. Brittle fracture dominates in FeCoNiAlSi0.2 and FeCoNiAlSi0.4 HEAs. A complete brittle fracture was noticed with river-like patterns in FeCoNiAlSi0.8 HEAs. The results of this investigation suggest that HEAs with different Si molar ratios and tuned phase structures can be used to design high-strength structural alloys for automotive applications.
Keywords: Body-centred cubic; Densifications; High entropy alloys; Metallic silicon; Molar ratio; Non-metallic; Phases transformation; Si addition; Silicon additions; Strengthening mechanisms; High entropy alloy; Mechanical alloying; Phase transformation; Powder metallurgy; Strengthening mechanism